Cadre Assistance in Improving Quality of Life Pregnant Women During the Covid-19 Pandemic - Christin Hiyana Tunggadewi; Ayuningtyas Ayuningtyas; Nuril Nikmawati; Mohammad Zen Rahfiludin (JURNAL KEBIDANAN, 2022)
The Covid-19 pandemic has become a non-natural disaster that has brought a lot of losses, and has been designated by the government as a national disaster. Pregnant women who were confirmed positive for Covid-19 in September 2020 were 4.9% of the total 1,483 confirmed cases. Vulnerable groups for Covid-19 infection are pregnant women, maternity, and newborns, which can increase the incidence of morbidity and mortality in mothers and babies. Pregnancy is a transitional period with important physical and emotional changes, the changes that occur can affect the quality of life of pregnant women and affect the health of mothers and babies. Modification of health services during the Covid-19 pandemic is needed when there is a change in essential health services, especially community-based health efforts by maximizing the function of health cadres. This type of research is a quasi-experimental with one group pre and post test with control group design. Sample number 15 pregnant women in the third trimester each group. The assistance of 1 cadre 1 pregnant women is carried out 1x/week for 3x, with activities including: learning material for the MCH Handbook as a substitute for classes for pregnant women, pregnancy exercise and providing material for service guidelines during the Covid-19 period. The research instrument is WHOQOL-BREF. The data normality test was carried out by Shapiro Wilk and the data analysis was carried out using the Wilcoxon Test. There is a significant effect of cadre assistance on the quality of life of pregnant women in the physical, psychological, social and environmental domains during the Covid-19 pandemic with p-value = 0.001 in all domains. The need for intensive assistance from health cadres to pregnant women during the Covid-19 pandemic to improve the quality of life.